P-255 Double vitrification and warming does not impact clinical pregnancy rate in single blastocyst transfer cycles. (30th June 2022) - Makieva, S; Sachs, M.K; Xie, M; Velasco, A; El-Hadad, S; Kalaitzopoulos, D.R; Dedes, I; Stiller, R; Leeners, B
Abstract: Study question: Does double vitrification and thawing impact clinical pregnancy rate after a single blastocyst transfer? Summary answer: The clinical pregnancy rate obtained after double vitrification was comparable to that obtained after single vitrification. What is known already: Double vitrification-warming (DVW) is commonly practiced to accommodate surplus viable embryos suitable for transfer, allow retesting of inconclusive-diagnosed blastocysts for PGT and circumvent limitations associated with national policies on embryo culture in certain countries. Despite its popularity, the evidence concerning the impact of DVW on IVF/ICSI outcomes is limited and lacking credibility. Biopsied blastocysts have comparable chance of clinical pregnancy following double and single round of vitrification. However, our study is the first to report clinical pregnancy outcomes following DVW in the absence of biopsy and in the case where the first round of vitrification occurred at the zygote stage. Study design, size, duration: This is a retrospective observational analysis of n = 452 single blastocyst transfers that were either vitrified-warmed once (SVW, n = 349) or twice (DVW, n = 103) between January 2017 and December 2021. Participants/materials, setting, methods: In the SVW group, blastocysts were vitrified on day 5/6 and warmed on the day of embryo transfer (ET). In the DVW group, zygotes (2PN) were first vitrified-warmed and then vitrified again on day 5/6 and warmed on the day of ET. Exclusion criteria were ETs from PGT and vitrified-warmed oocyte cycles. All ETs were performed at the University Hospital of Zurich in Switzerland following a spontaneous or artificial endometrial preparation. Main results and the role of chance: Mean maternal age at oocyte pick-up (OPU) and at ET did not differ between the two groups: at OPU: 35.1±4.4 and 35.9±4.1 years for DVW and SVW groups respectively (p = 0.106), at ET: 36.6±4.4 and 36.5±4.4 years for DVW and SVW respectively (p = 0.73). The causes of infertility did not differ between the groups (p = 0.87): male factor infertility was most common: 46.6% and 50.1% of cases for DVW and SVW respectively while other causes included idiopathic infertility, anovulation, endometriosis and polycystic ovarian syndrome. The rate of fertilisation method utilised was similar between the groups (p = 0.98): DVW had 71.8% ICSI and 29% IVF while SVW had 71.9% ICSI and 28% IVF. The quality of blastocysts at ET was equal in the two groups (p = 0.09): DVW had 33.9% top, 30.9% medium and 35.9% low quality blastocyst while SVW had 34.3% top, 31.2% medium and 34.3% low quality blastocysts. The blastocyst expansion grade at ET was similar between the groups (p = 0.087): DVW had 64.9% 3-4 expanded, 32% hatching and 2.9% hatched blastocysts while SVW had 75.8% 3-4 expanded, 21.7% hatching and 2.2% hatched blastocysts. The clinical pregnancy rate was comparable between the groups (p = 0.54): for DVW it was 46.6% and for SVW it was 43.2%. Limitations, reasons for caution: The study is limited by its retrospective nature and rather small cohort. Caution should be taken concerning interpretation of these findings in the case that double vitrification-warming occurs at different stages of embryo development. Wider implications of the findings: The result of the present study on double vitrification-warming procedure provides a framework for counselling couples on their chance of clinical pregnancy per warming cycle. It additionally provides confidence and reassurance to laboratory professionals in certain countries where national policies limit embryo culture strategies making DVW inevitable. Trial registration number: N/A